IMPACT OF MIGRATION PROCESS MANAGEMENT ON THE LABOR MARKET: https://doi.org/10.5281/zenodo.13833741 - Odilova , Feruza (Science technology&Digital finance, 2024)
The article explores the issues of state regulation of the labor market and the participation of young people in migration, who for the first time entered the labor market, taking into account the processes of managing migration processes in the conditions of modernization of the economy